2021
DOI: 10.3389/fpls.2021.744792
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics and Transcriptomics Reveals Differences in Proteins During Anthers Development in Oryza longistaminata

Abstract: Oryza longistaminata is an African wild rice species that possesses special traits for breeding applications. Self-incompatibility is the main cause of sterility in O. longistaminata, but here we demonstrated that its pollen vitality are normal. Lipid and carbohydrate metabolism were active throughout pollen development. In this study, we used I2-KI staining and TTC staining to investigate pollen viability. Aniline-blue-stained semithin sections were used to investigate important stages of pollen development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Three mounts were made for each group of samples, and five fields of view were observed for each mount. Pollen coloration rate = number of red pollen grains/total number of pollen grains × 100% [17][18][19] .…”
Section: Methodsmentioning
confidence: 99%
“…Three mounts were made for each group of samples, and five fields of view were observed for each mount. Pollen coloration rate = number of red pollen grains/total number of pollen grains × 100% [17][18][19] .…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, transcriptomic sequencing and proteomic integrated analysis have been widely used in plants on pollen development, fertility transition, and biological and abiotic stress responses to gain high-resolution data with great accuracy and efficiency [ 16 , 17 , 18 ]. They have also been applied to obtain key information regarding pollen development in various CMS mutants of cabbage, cotton, rice, and other crops [ 19 , 20 , 21 ]. Xing et al [ 22 ] found that the key differentially expressed genes (DEGs) participating in gibberellin-mediated tapetum-programmed cell death (PCD) pathways and sporopollenin biosynthesis were significantly related to the sterility phenotype in Ogu CMS line R2P2CMS using integrated RNA-seq and isobaric tags proteomic analysis.…”
Section: Introductionmentioning
confidence: 99%